Information services and research productivity in selected financial institutions in Metro Manila - Cabrera, Ma. Christina C.; Sison, Josephine C.; Santos, Herminia H. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
Financial institutions, just like other business organizations, require relevant, timely and accurate information for their operations. Banks use and value information for several reasons: 1) for complying with various guidelines and targets; 2) for helping bakns plan their operations and assess their own performance vis-a-vis the industry as a whole, in order to remain competitive; 3) for building up comprehensive profiles of existing and potential clients; and 4) information is used by central banks for economic and financial analysis, for the effective supervision of the individual institutions they regulate. This study was an investigation into the relationship between the research productivity of the different financial institutions in Metro Manila, and the use of information services available to them.
Of the 52 qualified financial institutions that were sent questionnaires, only 16 (31 percent) responded. From these 16 institutions, 160 analysts were sent questionnaires and 70 (43.5 percent) responded. The findings of the study are: 1) individual characteristics and institutional resources, in general, do affect the research productivity of economists and analysts of financial institutions; 2) most of the institutions have only the most basic information services, namely the ready-reference service; 3) in general, the factors belonging to the individual characteristics and institutional resources have significant relationships with the use of some of the information services; and 4) the use of information services does not in any way significantly increase the productivity of economists and analysts.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Information services -- Philippines -- Manila Metropolitan Area; Financial institutions -- Philippines -- Manila Metropolitan Area; Financial institutions -- Research -- Philippines -- Manila Metropolitan Area